(untitled) (Agro-Science Letters, 2026)
Whether farmers benefit more from pest management guidance provided by public agencies versus private entities affiliated with agrochemical companies remains a critical question in agricultural policy. Transitioning toward more sustainable farming depends fundamentally on the choices farmers make regarding technology and production inputs, choices that are shaped by access to information and peer learning. Advisory services are especially valuable when new or complex technologies are involved, supplementing knowledge gained through farmer-to-farmer exchange. Pest management decisions, in particular, are frequently guided by extension services, making these services central to contemporary agricultural policy debates. Global trends indicate that pest pressure is intensifying—driven partly by climate change and the growing commercialization of advisory services—while societal concern over pesticide-related environmental and public health risks continues to mount. Pesticide resistance is also emerging as a major challenge. In this context, extension services carry significant responsibility, as farmers’ pest management choices affect not only their own livelihoods but also the wellbeing of surrounding communities and the broader public. Consequently, extension guidance should be directed toward holistic strategies that maximize collective welfare.